The relationship between risk factors for falling and the quality of life in older adults - Ozdirenc Mehtap; Gelecek Nihal; Donat Hulya; Ozcan Ayse; Karadibak Didem (BMC, 2005)
Abstract Background Falls are one of the major health problems that effect the quality of life among older adults. The aim of this study was to explore the relationship between quality of life (Short Form-12) and the risk factors of falls (balance, functional mobility, proprioception, muscle strength, flexibility and fear of falling) in older adults. Methods One hundred sixteen people aged 65 or older and living in the T.C. Emekli Sandigi Narlidere nursing home participated in the study. Balance (Berg Balance test), functional mobility (Timed Up and Go), proprioception (joint position sense), muscle strength (back/leg dynamometer), flexibility (sit and reach) and fear of falling (Visual Analogue Scale) were assessed as risk factors for falls. The quality of life was measured by Short Form-12 (SF-12). Results A strong positive correlation was observed between Physical Health Component Summary of SF-12, General Health Perception and balance, muscle strength. Proprioception and flexibility did not correlated with SF-12 (p > 0.05). There was negative correlation between Physical Health Component Summary of SF-12, General Health Perception and fear of falling, functional mobility (p < 0.05). Conclusion We concluded that the risk factors for falls (balance, functional mobility, muscle strength, fear of falling) in older adults are associated with quality of life while flexibility and proprioception are not.